2013
DOI: 10.1002/jhm.2013
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of prophylactic inferior vena cava filters in patients undergoing bariatric surgery

Abstract: BACKGROUND The United States Food and Drug Administration recently issued a warning about adverse events in patients receiving inferior vena cava (IVC) filters. OBJECTIVE To assess relationships between IVC filter insertion and complications while controlling for differences in baseline patient characteristics and medical venous thromboembolism prophylaxis. DESIGN Propensity‐matched cohort study. SETTING The prospective, statewide, clinical registry of the Michigan Bariatric Surgery Collaborative. PATIENTS Bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
1
28
0
1
Order By: Relevance
“…Not all studies reported all outcomes. Mortality was not reported in studies by Halmi et al [9] , whereas the cause of death was not specified in all studies except Overby et al and Birkemeyer et al [7,12] .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Not all studies reported all outcomes. Mortality was not reported in studies by Halmi et al [9] , whereas the cause of death was not specified in all studies except Overby et al and Birkemeyer et al [7,12] .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 701 selected abstracts, we included 6 studies (n=102767) for the quantitative synthesis ( Figure 1) [7][8][9][10][11][12] . Studies were published between 2006 and 2013, and all patients underwent bariatric surgery ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2,6,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] We identified 12 retrospective studies about the prophylactic use of IVCF in bariatric surgery. [1,2,6,7,[10][11][12][13][14][15][16]26] One of the studies also had a prospective part in its study design. [11] In addition, one prospective study was found [17].…”
Section: Methodsmentioning
confidence: 99%